Relationship between weight-adjusted waist circumference index and prevalence of gallstones in U.S. adults: a study based on the NHANES 2017-2020 - Ke, Bin; Sun, Ying; Dai, Xin; Gui, Yang; Chen, Song (Frontiers in Endocrinology, 2023)
Objective We aimed to assess the association between weight-adjusted waist circumference index (WWI) and gallstone prevalence in US adults. Methods We selected individuals from the National Health and Nutrition Examination Survey (NHANES) database from 2017 to 2020 and used logistic regression analyses, subgroup analyses, and dose-response curves to assess the association between WWI and gallbladder stone prevalence and age, sex, and ethnicity. Results A total of 7971 participants aged ≥20 years were enrolled in our study; 828 patients had a self-reported history of gallstones. After correcting for confounders, for each unit of WWI after Ln conversion, the prevalence of gallbladder stones increased by 34% (OR=1.34, 95% CI:1.20, 1.50). Dose-response curves showed a positive correlation between WWI and gallbladder stone prevalence.According to the subgroup analysis, the positive association between TyG index and high-frequency HI was more significant in males(OR=1.34, 95% CI:1.07, 1.69), <40 years old(OR=1.42, 95% CI:1.18, 1.71), white people Americans(OR=1.35, 95% CI:1.08, 1.68) and other races(OR= 1.56, 95% CI:1.13, 2.14). Conclusion Higher WWI was positively associated with the prevalence of gallbladder stones and was associated with gender, age, and ethnicity. This is noteworthy, although a causal relationship could not be established.